Penerjemahan Makian dalam Webtoon Yakhan Yeongung ke dalam Bahasa Indonesia - Ratu Syarifa Nurazizah; Usmi Usmi (Universitas Gadjah Mada, 2021)
Profanity is an expression used by someone for the purpose of berating, slandering, or expressing their anger towards others. In Korean, profanity also has another purpose, which is to show intimacy between the speakers and their partner. The purpose of this research is to explain how Korean profanity is translated into Indonesian in the webtoon Yakhan Yeongung. This research uses a descriptive analysis method with a qualitative approach and archival study as the research technique. This research includes Chang’s profanity classification theory as well as Vinay and Dalbernet’s translation theory as references. This research concludes that from the 28 profanity words identified in the data, 15 of them are simple profanities while the rest are compound profanities. Among those, there are two simple profanities and a compound profanity that were not translated. The translation methods used to translate these two kinds of profanity are also different. The simple profanity is translated using literal translation, transposition, equivalence and adaptation methods. Meanwhile, the compound profanity is translated using transposition, equivalence, adaptation, deletion and addition methods.